The Untold Story of Midijobs - Riphahn, Regina Therese; Herget, Anna (Jahrbücher für Nationalökonomie und Statistik, 2022)
Midijobs are employment relationships with moderate monthly earnings that benefit from payroll tax subsidies. Since 2003, the subsidy is universally available for all regions, industries, individuals, and employers in Germany. Recently, more than 2.9 million individuals, i.e., almost 9 percent of the German labor force covered by the social security system took advantage of Midijobs. This paper describes the program, its motivation, and utilization over time. We characterize the labor market transitions leading into and out of Midijob employment, the duration of Midijob utilization, and compare recent developments with patterns of program utilization that were observed early on.
CRIS-Team WoS Importer:2022-04-29
Keywords: Midijobs; Minijobs; payroll tax subsidy; SIAB; Chancengleichheit